COL2-dependent photoperiodic floral induction in Nicotiana sylvestris seems to be lost in the N. sylvestris × N. tomentosiformis hybrid N. tabacum - Schmidt, Florentin J.; Grundmann, Lena; Lahme, Michael; Seidemann, Marvin; Schwarze, Axel; Lichtenauer, Sophie; Twyman, Richard M.; Prüfer, Dirk; Noll, Gundula A. (Frontiers in Plant Science, 2024)
Introduction Plants are sessile organisms that maximize reproductive success by adapting to their environment. One of the key steps in the reproductive phase of angiosperms is flower development, requiring the perception of multiple endogenous and exogenous signals integrated via a complex regulatory network. Key floral regulators, including the main transcription factor of the photoperiodic pathway (CONSTANS, CO) and the central floral pathway integrator (FLOWERING LOCUS T, FT), are known in many species. Methods and results We identified several CO-like (COL) proteins in tobacco (Nicotiana tabacum). The NtCOL2a/b proteins in the day-neutral plant N. tabacum were most closely related to Arabidopsis CO. We characterized the diurnal expression profiles of corresponding genes in leaves under short-day (SD) and long-day (LD) conditions and confirmed their expression in phloem companion cells. Furthermore, we analyzed the orthologs of NtCOL2a/b in the maternal LD ancestor (N. sylvestris) and paternal, facultative SD ancestor (N. tomentosiformis) of N. tabacum and found that they were expressed in the same diurnal manner. NtCOL2a/b overexpression or knock-out using the CRISPR/Cas9 system did not support a substantial role for the CO homologs in the control of floral transition in N. tabacum. However, NsCOL2 overexpression induced flowering in N. sylvestris under typically non-inductive SD conditions, correlating with the upregulation of the endogenous NsFTd gene. Discussion Our results suggest that NsFTd is transcriptionally regulated by NsCOL2 and that this COL2-dependent photoperiodic floral induction seems to be lost in N. tabacum, providing insight into the diverse genetics of photoperiod-dependent flowering in different Nicotiana species.